Influence of Cedar Essential Oil on Physical and Biological Properties of Hemostatic, Antibacterial, and Antioxidant Polyvinyl Alcohol/Cedar Oil/Kaolin Composite Hydrogels - Tamer M. Tamer; Maysa M. Sabet; Zahrah A. H. Alhalili; Ahmed M. Ismail; Mohamed S. Mohy-Eldin; Mohamed A. Hassan (MDPI AG, 2022)
Polyvinyl alcohol (PVA) is a safe and biodegradable polymer. Given the unique physical and chemical properties of PVA, we physically cross-linked PVA with kaolin (K) and cedar essential oil (Ced) using the freeze-thawing approach to fabricate PVA/Ced/K sponge hydrogels as hemostatic, antibacterial, and antioxidant wound healing materials. The physicochemical characteristics of PVA/Ced/K hydrogels, including water swelling profiles and gel fractions, were surveyed. Additionally, the functional groups of hydrogels were explored by Fourier transform infrared spectroscopy (FTIR), while their microstructures were studied using scanning electron microscopy (SEM). Furthermore, the thermal features of the hydrogels were probed by thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC). Evidently, alterations in cedar concentrations resulted in significant variations in size, water uptake profiles, and hydrolytic degradation of the hydrogels. The incorporation of cedar into the PVA/K endowed the hydrogels with significantly improved antibacterial competency against Bacillus cereus (B. cereus) and Escherichia coli (E. coli). Moreover, PVA/Ced/K exhibited high scavenging capacities toward ABTS•+ and DPPH free radicals. Beyond that, PVA/Ced/K hydrogels demonstrated hemocompatibility and fast blood clotting performance in addition to biocompatibility toward fibroblasts. These findings accentuate the prospective implementation of PVA/Ced/K composite hydrogel as a wound dressing.